Emergency department utilisation among older people with acute and/or chronic conditions: A multi-centre retrospective study. (March 2018) - Fry, Margaret; Fitzpatrick, Lesley; Considine, Julie; Shaban, Ramon Z.; Curtis, Kate
Highlights: Older persons with acute illnesses are likely to be admitted than those with chronic conditions. Older persons with chronic conditions present less frequently and have higher discharge rates. Patients with acute conditions present frequently, receive higher triage categories and have higher admission rates. Abstract: Introduction: Older persons aged over 65 years represent up to 41% of Australian Emergency Department (ED) presentations. Older persons present with acute and/or chronic conditions, have more Emergency Department visits, hospital admissions and readmissions than other age groups. However, little is known about the characteristics and trends of acute illness and chronic presentations and whether frailty changes these dimensions within this cohort. Methods: A 12-month retrospective medical record audit of persons over 65 years presenting to four EDs. Results: Data from 44, 774 (26.6%) patients aged 65 years and over were analysed. Patients with acute conditions presented more frequently (n = 30, 373; 67.8%), received more urgent triage categories (n = 13, 471; 30.1%) and had higher admission rates (n = 18, 332; 61%). Chronic conditions presented less frequently (n = 14, 396; 32.1%) and had higher discharge rates (n = 9302; 65%). Patients over 80 years were allocated more urgent triage categories and commonly presented with falls (n = 3814; 8.5%). Patients between 65 and 79 years had a higher discharge rate (n = 10, 397; 46.1%). Conclusion: Older persons with acute illnesses were more likely to be admitted than those with chronic conditions and who were more likely to be discharged home. There is scope for further investigation of new models of care to better manage older persons with chronic conditions and ED discharge practices.